Healthcare Resource Availability, Quality of Care, and Acute Ischemic Stroke Outcomes - O'Brien, Emily C. (J Am Heart Assoc, 2017)
BACKGROUND: Healthcare resources vary geographically, but associations between hospital‐based resources and acute stroke quality and outcomes remain unclear. METHODS AND RESULTS: Using Get With The Guidelines‐Stroke and Dartmouth Atlas of Health Care data, we examined associations between healthcare resource availability, stroke care, and outcomes. We categorized hospital referral regions with high‐, medium‐, or low‐resource levels based on the 2006 national per‐capita availability median of 6 relevant acute stroke care resources. Using multivariable logistic regression, we examined healthcare resource level and in‐hospital quality and outcomes. Of 1 480 308 admitted ischemic stroke patients (2006–2013), 28.8% were hospitalized in low‐, 44.4% in medium‐, and 26.9% in high‐resource hospital referral regions. Quality‐of‐care/timeliness metrics, adjusted length of stay, and in‐hospital mortality were similar across all resource levels. CONCLUSIONS: Significant variation exists in regional availability of healthcare resources for acute ischemic stroke treatment, yet among Get With the Guidelines‐Stroke hospitals, quality of care and in‐hospital outcomes did not differ by regional resource availability.